Waterless sterilization and cleaning of sheep wool fiber using supercritical carbon dioxide. Issue 5 (March 2022) - Allafi, Faisal Aboelkasim; Hossain, Md Sohrab; Shaah, Marwan; Lalung, Japarang; Ab Kadir, Mohd Omar; Ahmad, Mardiana Idayu
There is increasing concern regarding the existing sheep wool processing technology in the textile industry owing to the enormous volume of toxic effluents generated. The application of supercritical carbon dioxide (scCO2 ) in sheep wool processing is cleaner and increases wool fiber production while avoiding toxic effluent generation. scCO2 is a novel clean technology that can be utilized in sheep processing for sterilization, cleaning, and drying sheep wool at the same time. In the present study, scCO2 was used to treat sheep wool with varying pressure, temperature, and treatment time. These parameters influence the scCO2 treatment of sheep wool fiber through the inactivation of microorganisms and improvement of the whiteness index. The identification of bacteria in sheep wool was carried out based on biochemical analysis by molecular means, using 16s rRNA sequencing. It was found that scCO2 completely inactivated the microorganisms present in sheep wool and potentially enhanced the percentage whiteness index at the highest pressure of 30 MPa, temperature of 80°C, and treatment time of 80 min. Several analytical methods were employed to assess the physicochemical, thermal, and morphological properties of untreated and scCO2 treated sheep wool fibers. The results show that scCO2 effectively removes the impurities and completely inactivates the microorganisms present in sheep wool. The findings of the present study reveal that scCO2 can be utilized as an alternative treatment technology for sheep wool processing in the textile industry.